PENERAPAN PENDEKATAN SAINTIFIK BERBANTUKAN MEDIA APLIKASI ARTICULATE STORYLINE 3 PADA MATERI HUKUM NEWTON UNTUK MENINGKATKAN HASIL BELAJAR FISIKA SISWA KELAS X MIA SMA N 1 MANDAH - Dona Permata Sari; Azizahwati Azizahwati; Azhar Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : This research aims to improve the learning outcomes of students of class X MIA SMA N 1 Mandah with the application of scientific approach slammed media application Articulate Storyline 3, and to find out the difference between the results of learning physics of class students who apply scientific approach slammed media application articulate storyline 3 with conventional classes. This type of research is quantitative using quasi experiment methods, and the design used is pretest-posttest control group design. The sample in the study was 56 students, 28 students of class X MIA 1 and 28 students of class X MIA 2. Data analysis is done with descriptive analysis as well as inferential analysis using parametric statistics. The results of this study showed the results of learning physics students with the application of scientific approaches assisted by articulate storyline application media 3 with an average score of 74.88 higher than the results of learning physics with conventional learning with a score of 74.88 higher than the results of studying physics with conventional learning with a score of 74.88 physics.Key Word : Learning Media, Articulacate Storyline 3, Newton's Law